Antipodal Tattooing: Muslim Youth in Chinese Gangs. Issue 8 (2nd August 2016) - Nasir, Kamaludeen Mohamed
ABSTRACT: The relationship between Muslims and body art has not been a subject of academic inquiry. This is strange since tattooing has become more prevalent in many urban cosmopolitan cities. This article examines the tattooing practices of Muslim men in Singapore. These practices are sociologically interesting because they involve Malay men who are predominantly Muslims, tattooing themselves as part of their membership in gangs that are mostly Chinese-dominated. This article presents the concept of "antipodal tattooing, " which can be instructive in understanding the relationships between tattooing and identity formation as expressions of the fragile and fragmented character of minority youth identities in urban life.